Assessing Ergonomic Risk Loads on Pilots Across Diverse Aircraft Types - Ibrahim T. Ucar; Selcuk Cebi (Havacılık ve Uzay Teknolojileri Dergisi)
Work-related musculoskeletal disorders (WMSDs) are health problems that occur in muscles, tendons, ligaments, joints, and nerves as a result of exposure to ergonomic risk factors in the workplace. Ergonomic risk burden is a measure of a worker's risk of developing musculoskeletal disorders (MSDs) at work. This risk arises from exposure to ergonomic risk factors. Like many occupational groups, pilots are likely to be exposed to similar threats. They work in ergonomically demanding conditions such as prolonged static postures, vibration, and repetitive movements and are exposed to various risks. This increases the risk of developing musculoskeletal disorders. WMSD is one of the leading causes of unemployment and disability among pilots and can lead to long-term health problems. The Quick Exposure Check (QEC) method is a tool that can be used to quickly and easily assess pilots' exposure to these risk factors. This paper presents an application of the Quick Exposure Check method on pilots in the aviation field. It was assessed that different aircraft types may create different ergonomic risk burdens on pilots and the body parts at risk from ergonomic exposure were determined as back, shoulder/arm, wrist/hand and neck.